1993
DOI: 10.1016/s0006-3495(93)81237-2
|View full text |Cite
|
Sign up to set email alerts
|

Simulated formation of polymer domains in sickle hemoglobin

Abstract: Using experimentally observed processes of linear growth, heterogeneous nucleation, and polymer bending, with no additional assumptions, we have been able to model the two-dimensional formation of polymer domains by sickle hemoglobin. The domains begin with twofold symmetry and proceed toward closure into spherulites at a constant rate. Relationships derived from the simulations presented and the requirements of scaling result in simple expressions for the sensitivity of the closure times to the model input pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…On the contrary, the angular widening of the polymer domain, originated from the fiber branching, is largely suppressed for smaller heterogeneous nucleation rate as observed in both experiments 14 and numerical simulations. 15 Remarkably, this tendency is also consistent with the inverse relationship between the amount of intracellular aligned hemoglobin polymer and the mean corpuscular hemoglobin concentration values for each class of cells (categorized by the total number of polymer domains) reported in ref. 9.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…On the contrary, the angular widening of the polymer domain, originated from the fiber branching, is largely suppressed for smaller heterogeneous nucleation rate as observed in both experiments 14 and numerical simulations. 15 Remarkably, this tendency is also consistent with the inverse relationship between the amount of intracellular aligned hemoglobin polymer and the mean corpuscular hemoglobin concentration values for each class of cells (categorized by the total number of polymer domains) reported in ref. 9.…”
Section: Introductionsupporting
confidence: 89%
“…This configuration prevails with the physiological conditions of low mean corpuscular hemoglobin concentration value and slow deoxygenation rate, where the sickle hemoglobin heterogeneous nucleation is largely suppressed, as observed in experiments 9 and predicted by simulations. 15 Accordingly, we choose the mean corpuscular hemoglobin concentration value as 32 g dL −1 , where the bulk growth rate is 1.2 × 10 4 molecules s −1 . Moreover, we note that the aligned hemoglobin polymer domain may deflect along the z direction due to the heterogeneous growth.…”
Section: Resultsmentioning
confidence: 99%
“…With a simple model invoking documented polymer bending as well as heterogeneous nucleation, Dou & Ferrone previously showed that the shape of domains begins with a 2-fold symmetry that fans into a spherical shape, referred to as domain closure, after a period of time. 18 If the bending rate is b, then the time for domain closure was found to vary as 1=…”
Section: Domain Structure Of Hb S/f or Hb S/a β73leu Mixturesmentioning
confidence: 99%
“…To this end, Dou and Ferrone developed a kinetic model for sickle hemoglobin polymerization to understand domain formation. Their qualitative results showed that the transformation of a single fiber into wheat-sheaf bundles and then to spherulitic domains (Dou and Ferrone 1993). Dynamic simulations of self-assembly of sickle hemoglobin confirmed that chain chirality is the main driver for the formation of sickle hemoglobin fibers (Li et al 2012c).…”
Section: Dynamics Of Deformable Particles In Dilute Suspensionsmentioning
confidence: 99%